Konseling Islam Untuk Mengatasi Masalah Psikologi Remaja Dampak Perceraian Orang Tua (Studi Kasus Pada Klien “H” Di Desa Pulau Harapan) - Nurkholis Abdillah; Kusnadi; Mana Rasmanah (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This research is entitled Islamic Counseling to Overcome Adolescent Psychological Problems Impact of Parental Divorce (Case Study of Client "H" in Pulau Harapan Village). Islamic counseling is one of the repressive steps in taking further action against the psychological problems of teenagers as a result of divorce. The aim of this research is firstly, to find out what the condition of teenage victims of parental divorce is in client "H" in Pulau Harapan Village, then secondly, to find out how individual counseling is applied to client "H" in Pulau Harapan Village and thirdly, to find out what the conditions are like. teenagers after implementing individual counseling. This type of research is field research, a qualitative approach, and uses case study research methods. The subjects in this research were Client "H" and Relatives of Client "H". Data collection tools in this research are observation, interviews and documentation. The results of this research show that during his parents' divorce, Klian "H" was often gloomy and silent and even became over-controlled, namely by drinking alcohol and even taking drugs. Furthermore, after an Islamic counseling approach was carried out, namely by being given suggestions for religious advice, encouragement and motivation were given, so that as a result of the Islamic counseling guidance process, Client "H" was able to feel calm and accept the conditions as they were.